2016
DOI: 10.1186/s12891-016-1185-6
|View full text |Cite
|
Sign up to set email alerts
|

Drug retention and safety of TNF inhibitors in elderly patients with rheumatoid arthritis

Abstract: BackgroundThe concerns about the development of adverse events (AEs) in elderly RA patients as a result of age-related changes in drug metabolism and the presence of comorbid illnesses are emphasizing due to increasing prevalence of rheumatoid arthritis (RA) in old age. However, they tend to be inadequately represented in RA clinical trials because of the exclusion criteria that are commonly applied. The tolerability and safety of TNF inhibitors in elderly patients have not been also evaluated in clinical prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 28 publications
(29 reference statements)
1
21
1
2
Order By: Relevance
“…[19][20][21][22][23][24][25][26][27][28][29][30][31] Thus, our final analysis included 14 unique studies. [7][8][9][32][33][34][35][36][37][38][39][40][41][42] Of these, 3 studies had only the abstract available for review, but sufficient detailed information could be extracted to allow for inclusion. 9,41,42 Most studies were retrospective cohorts; only 2 were prospective studies.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23][24][25][26][27][28][29][30][31] Thus, our final analysis included 14 unique studies. [7][8][9][32][33][34][35][36][37][38][39][40][41][42] Of these, 3 studies had only the abstract available for review, but sufficient detailed information could be extracted to allow for inclusion. 9,41,42 Most studies were retrospective cohorts; only 2 were prospective studies.…”
Section: Literature Searchmentioning
confidence: 99%
“…Of these 14 studies, 6 were among patients with IBD (n ¼ 349 older biologic patients), 7,8,32,33,41,42 1 study included those with psoriasis (n ¼ 135 older biologic patients), 40 and 7 examined those with RA (n ¼ 4235 older biologic patients). 9,[34][35][36][37][38][39] The mean age of included participants was 71 years of age for older biologic users (data from 11 studies), 43 years of age for younger biologic users (data from 10 studies), and 72 years of age in the older nonbiologic control patients (data from 6 studies). More than half the patients in each subgroup were women: 61% of older biologic users (9 studies), 65% of younger biologic users (8 studies), and 51% of older control subjects (3 studies).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Previous studies have reported the safety and effectiveness of biologic disease-modifying antirheumatic drugs (bDMARDs) directed against tumor necrosis factor (TNF) and interleukin (IL)-6 receptor for the treatment of RA; caution has been raised regarding their use in elderly patients [4,5]. These reports suggested that the risk-benefit balance should be carefully considered, particularly for elderly patients who will receive these medications [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this notion is supported by previous studies demonstrating that poor treatment persistence of biologics can blunt the effectiveness [22,23]. While several studies have revealed that overall treatment persistence of biologic agents in elderly RA patients is not inferior to that in younger RA patients [24,25], large variation in treatment persistence as well as reasons for discontinuation among different biologic agents have been noted [25,26]. As to GLM, there are no published studies on treatment persistence measured for patients aged 75 years or above in real-world practice in Japan.…”
Section: Introductionmentioning
confidence: 71%